The effect of maternal caffeine consumption during the perinatal period on lactation - Tigka, Maria; Nanou, Christina; Tzeli, Maria; Gryparis, Alexandros; Metallinou, Dimitra; Lykeridou, Aikaterini (Health & Research Journal, 2024)
Background: Caffeine is a substance found in various seeds, foods, beverages and pharmaceuticals. We sought to assess perinatal caffeine consumption rates and the impact of maternal consumption on lactation. Material and Method: This is a prospective, descriptive cohort study conducted in Greece. Women were recruited from five tertiary maternity hospitals throughout 2020. A total of 847 mothers participated and data were collected during their hospitalization in the maternity hospital using a structured questionnaire. Follow-up included a telephone interview in the first, third and sixth month after delivery. Results: A significant decrease in caffeine consumption was reported during pregnancy (84.7%) compared to the period before pregnancy (96.3%, p<0.001). On the fourth day postpartum, caffeine intake (65.8%) was reduced significantly compared to the pre-pregnancy period (p<0.001), remaining relatively unchanged over a period of three months postpartum (1st month: 71%, 3rd month: 64.7%). Moreover, there was a significant decline in caffeine intake at six months postpartum (54.2%, p<0.001) and after discontinuation of breastfeeding (42.7%, p<0.001). Our findings showed that women who ceased breastfeeding at any stage over the six-month follow-up consumed less caffeine during the first three months after delivery (p<0.001) in comparison to those who maintained breastfeeding at six months. In addition, higher pre-pregnancy caffeine consumption (β = 0.04, SE: 0.02, p = 0.032) had a positive association with longer breastfeeding duration. Conclusions: Τhis study was the first to record caffeine intake in the perinatal period in the Greek setting. The results demonstrate that perinatal maternal caffeine consumption was reduced compared to the pre-pregnancy period and that there was a positive correlation between caffeine consumption and breastfeeding duration.